Small worlds : the dynamics of networks between order and randomness - Watts, Duncan J., 1971- (Princeton studies in complexity., 1999)
The small-world phenomenon states that, soon after meeting a stranger, we are surprised to discover that we are connected through a short chain of acquaintances. This text provides an exploration of the conditions in which a small world can arise.